Successful Visual Rehabilitation After Penetrating Ocular Trauma via Yamane Scleral Fixation: A Case Report - Nursalim, Ade J.; Emily, Ardelia (e-CliniC, 2026)
Abstract: Penetrating ocular trauma frequently leads to traumatic cataract with capsular and zonular disruption, complicating standard in-the-bag intraocular lens (IOL) implantation. Sutureless intrascleral fixation (Yamane technique) offers a minimally invasive posterior chamber IOL option that avoids long-term suture-related complications. We reported a 68-year-old woman presented one day after penetrating needle injury to the right eye with uncorrected visual acuity (UCVA) 1/300, full-thickness corneal laceration (positive Seidel), anterior capsule tear, and zonular dialysis from 7 to 1 o’clock with lens fragments in the anterior chamber. Under retrobulbar anesthesia, corneal wound closure was performed with interrupted 10-0 nylon, followed by cataract extraction and anterior vitrectomy. In the same operation, two transconjunctival sclerotomies were created 2.0 mm posterior to the limbus (superonasal and superotemporal) using 27-gauge thin-walled needles at ~20°. A three-piece foldable IOL was implanted by the Yamane flanged-haptic technique; haptics were externalized, cauterized to 0.3–0.5 mm flanges, and tucked into scleral tunnels. The IOL centered well without tilt; no conjunctival peritomy was required. Postoperatively, UCVA improved to 1/60 on day 1, 6/60 at 2 weeks (after suture removal), and 6/15 at 1 month (6/6 with pinhole). In three-month follow-up, the retina remained attached, intraocular pressure was stable, no cystoid macular edema, and the IOL remained well positioned. In conclusion, in complex open-globe injury with inadequate capsular support, single-session repair with immediate Yamane sutureless scleral fixation of a three-piece IOL can achieve rapid, stable visual recovery and anatomic stability in geriatric eyes. Careful wound closure, symmetric needle entry, and precise flange creation are key to IOL centration and complication avoidance; continued follow-up is advised to monitor long-term flange stability. Keywords: penetrating ocular trauma; traumatic cataract; zonular dialysis; scleral fixation; Yamane technique